Psychometric properties of alcohol screening tests in Emergency Departments in Argentina, Mexico and the United States - Cremonte, Mariana (2010)
The objective of this article is to report psychometric characteristics of the AUDIT, CAGE, RAPS4, and TWEAK and to compare them across three countries: Argentina, Mexico, and the United States which used a similar protocol and methodology. Probability samples of patients 18 years and older were drawn from emergency departments in Mar del Plata, Argentina (n=780), Pachuca, Mexico (n=1624) and Santa Clara, U.S. (n=1220). Concurrent validity was assessed by comparing their performance against a diagnosis of alcohol dependence (DSM-IV) obtained through the Composite International Diagnostic Interview, and for the briefer measures, also by their correlation with the AUDIT. The internal consistency of the CAGE, RAPS4, and TWEAK scores was estimated by the KR-20 formula and by Cronbach?s Alpha for the AUDIT. Corrected item-total correlation and D-values were used as item discrimination measures. In Argentina and Mexico the AUDIT and the RAPS4 showed the highest validity. Reliability of all instruments was higher in the US than in Argentina or Mexico. In all three countries, reliability of the TWEAK was lowest, while the AUDIT was highest. With a few exceptions, all items showed good discrimination powers.